Growth and characterization of CNT–TiO2 heterostructures - Zhang, Yucheng; Utke, Ivo; Michler, Johann; Ilari, Gabriele; Rossell, Marta D.; Erni, Rolf (Beilstein Journal of Nanotechnology, 2014)
A thriving field in nanotechnology is to develop synergetic functions of nanomaterials by taking full advantages of unique properties of each component. In this context, combining TiO2 nanocrystals and carbon nanotubes (CNTs) offers enhanced photosensitivity and improved photocatalytic efficiency, which is key to achieving sustainable energy and preventing environmental pollution. Hence, it has aroused a tremendous research interest. This report surveys recent research on the topic of synthesis and characterization of the CNT–TiO2 interface. In particular, atomic layer deposition (ALD) offers a good control of the size, crystallinity and morphology of TiO2 on CNTs. Analytical transmission electron microscopy (TEM) techniques such as electron energy loss spectroscopy (EELS) in scanning transmission mode provides structural, chemical and electronic information with an unprecedented spatial resolution and increasingly superior energy resolution, and hence is a necessary tool to characterize the CNT–TiO2 interface, as well as other technologically relevant CNT–metal/metal oxide material systems.
Keywords: atomic layer deposition (ALD); carbon nanotubes; electron energy loss spectroscopy (EELS); interface; titanium dioxide (TiO2); transmission electron microscopy (TEM)